Past history shapes evolution of reproductive success in a global warming scenario. (February 2023) - Santos, Marta A.; Antunes, Marta A.; Grandela, Afonso; Carromeu-Santos, Ana; Quina, Ana S.; Santos, Mauro; Matos, Margarida; Simões, Pedro
Abstract: Adaptive evolution is critical for animal populations to thrive in the fast-changing natural environments. Ectotherms are particularly vulnerable to global warming and, although their limited coping ability has been suggested, few real-time evolution experiments have directly accessed their evolutionary potential. Here, we report a long-term experimental evolution study addressing the evolution of Drosophila thermal reaction norms, after ∼30 generations under different dynamic thermal regimes: fluctuating (daily variation between 15 and 21 °C) or warming (daily fluctuation with increases in both thermal mean and variance across generations). We analyzed the evolutionary dynamics of Drosophila subobscura populations as a function of the thermally variable environments in which they evolved and their distinct background. Our results showed clear differences between the historically differentiated populations: high latitude D. subobscura populations responded to selection, improving their reproductive success at higher temperatures whereas their low latitude counterparts did not. This suggests population variation in the amount of genetic variation available for thermal adaptation, an aspect that needs to be considered to allow for better predictions of future climate change responses. Our results highlight the complex nature of thermal responses in face of environmental heterogeneity and emphasize the importance of considering inter-population variation in thermal evolution studies. Highlights: Evolution of thermal reaction norms was studied in two Drosophila subobscura populations. Northern European populations under warming selection improved reproductive success at high temperatures. Southern European population did not show evolution of thermal reaction norms under warming selection. Other life-history traits such as fecundity and juvenile viability did not show relevant changes. This study indicates population variation in the evolutionary potential for long-term thermal adaptation.